2003
DOI: 10.2460/ajvr.2003.64.773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin test reactivity to environmental allergens in healthy cats and cats with atopic dermatitis

Abstract: Skin test reactivity in cats should be evaluated after IV administration of 10% fluorescein solution by means of a Prausnitz-Küstner test to differentiate among IgE-mediated, IgG-mediated, and nonspecific reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…It was recently reported that the irritancy thresholds for IDT allergens in cats may need to be changed and that many ‘positive allergen reactions’ may in fact be due to irritant reactions 18 . However, in another study, no evidence of irritancy was found 19 . In the study reported here, if the positive reactions were caused by irritancy, it seems reasonable that a similar proportion of normal cats would have had false‐positive allergen reactions, but this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…It was recently reported that the irritancy thresholds for IDT allergens in cats may need to be changed and that many ‘positive allergen reactions’ may in fact be due to irritant reactions 18 . However, in another study, no evidence of irritancy was found 19 . In the study reported here, if the positive reactions were caused by irritancy, it seems reasonable that a similar proportion of normal cats would have had false‐positive allergen reactions, but this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…Among the animals of atopic dermatitis, the mouse, guinea pig (Fukuda et al, 2003), cat (Schleifer and Willemse, 2003), dog (Mueller et al, 2004) and horse (Lorch et al, 2001) are used. Mouse model of atopic dermatitis gets wider acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Different species including mice, dogs, cats and horses have been reported to develop AE-like skin lesions [13, 14, 15]. AE-like symptoms in dogs, cats or horses are diseases present in these domestic companions and are treated as disease states by veterinarians.…”
Section: Mouse Models Of Aementioning
confidence: 99%